2013
DOI: 10.1007/s00253-013-4767-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an acid-tolerant β-1,4-glucosidase from Fusarium oxysporum and its potential as an animal feed additive

Abstract: An extracellular β-glucosidase (BGL) from Fusarium oxysporum was purified to homogeneity by a single chromatography step on a gel filtration column. The optimum activity of BGL on cellobiose was observed at pH 5.0 and 60 °C. Under the same conditions, the K(m) and V(max) values for p-nitrophenyl β-D-glucopyranoside and cellobiose were 2.53 mM, 268 U mg protein(-1) and 20.3 mM, 193 U mg protein(-1), respectively. The F. oxysporum BGL enzyme was highly stable at acidic pH (t 1/2 = 470 min at pH 3). A commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…These changes along with viscosity reduction may result in better digestion and higher feed conversion ratio (FCR) in poultry. This is in agreement with the results of other researchers who observed that adding the enzyme to the poultry feed would improve digestion and eliminate digestive problems (Tervila-Wilo et al, 1996;Teymouri et al, 2018;Zhao et al, 2013).…”
Section: Effect Of the Enzyme On The Structure Of Cereal Grainssupporting
confidence: 93%
“…These changes along with viscosity reduction may result in better digestion and higher feed conversion ratio (FCR) in poultry. This is in agreement with the results of other researchers who observed that adding the enzyme to the poultry feed would improve digestion and eliminate digestive problems (Tervila-Wilo et al, 1996;Teymouri et al, 2018;Zhao et al, 2013).…”
Section: Effect Of the Enzyme On The Structure Of Cereal Grainssupporting
confidence: 93%
“…The optimal temperature of the purified β‐glucosidase is 60 °C, which is similar to those of other known ones from some microorganisms, such as Fusarium oxysporum (60 °C) , Aspergillus fumigates (60 °C) , the protoplast fusant of Aspergillus oryzae and A. niger (65 °C) , and Colletotrichum graminicola (65 °C) . Compared to many acidic β‐glucosidases from Sporidiobolus pararoseus (pH 4.0) , A. niger (pH 4.0) , Penicillium aculeatum (pH 4.5) , Oenococcus oeni (pH 5.0–5.5) , and Endophytic fungi (pH 5.0 and 6.0) , the β‐glucosidase from Bacillus sp.…”
Section: Discussionsupporting
confidence: 53%
“…Different Fusarium oxysporum species (more related to Fsh13) expressing different cellulases. The Fusarium oxysporum KCTC 16909 has one GH1, a β-glucosidase, [ 69 ] with 268 U/mg for the purified enzyme. Another Fusarium oxysporum [ 70 ] has at least two GH7, endoglucanases Cel7A [ 70 ] and Cel7B also known as endoglucanase I (PDB code 1OVW) [ 71 ].…”
Section: Discussionmentioning
confidence: 99%